Keeping to the set path enhanced storage stability for dry-mix mortars based on calcium aluminate - Estival, Jaques; Taquet, Pascal; Götz-Neunhoeffer, Friedlinde (European Coatings Journal, 2012)
Storage under high humidity can adversely affect the properties of dry mix mortars containing hydraulic binders. A new functionalised Calcium Aluminate Cement (CAC) has been developed with the aim of stabilising mortar reactivity during storage. Both setting kinetics and other properties such as shrinkage, porosity and linear size variations were found more robust over storage in humid conditions.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LM.keepin